Practical Oracle E-Business Suite An Implementation and Management Guide - Zaheer, Syed; Arslan, Erman (Apress : Imprint: Apress, 2016)
This book is a hands-on, real-world guide to building and implementing a robust Oracle E-Business Suite System using the new Release, EBS 12.2. It explains the rationale for using an Oracle E-business suite environment in a business enterprise and covers the major technology stack changes from EBS version 11i through R12.2. The book clarifies how to build up an EBS environment from a simple single-node installation to a complex multi-node high available setup. Practical Oracle E-Business Suite focuses on release R12.2, but key areas in R12.1 are also covered wherever necessary. Oracle E-Business suite R12.2 includes major changes in Technology Stack components and introduced many new features. And these changes and new features must be added to the skill set of those individuals responsible for implementing and managing Oracle EBS. Practical Oracle E-Business Suite provides detailed instructions for the Installation of EBS R12.2 in single and multi-node configurations, the logic and methodology used in EBS patching, and cloning of EBS single-node and complex multi-node environments configured with RAC. This book also provides filtered valuable information about such areas as FMW used in EBS 12.2, as well as performance tuning and EBS 12.2 on engineered system implementations. The following are the key areas of coverage: Introduction to Oracle E-Business Suite, general definition of the EBS product families and the overview of the new system architecture implemented in EBS 12.2 EBS 12.2 single node/multi-node installations along with the EBS 12.2 upgrades EBS 12.2 Application and database tier components along with details about the newly introduced EBS 12.2 FMW components, the new application filesystem (dual fs) and the new patching concept called online patching. Administration utilities including adconfig and rapid clone, along with their usages for managing and maintaining the EBS 12.2 systems. Security features and key areas for performance tuning in EBS 12.2 Implementing EBS 12.2 on Engineered Systems(Exadata, ODA and Exalogic).